Proceedings of the 17th meeting Working Group on Prolamin Analysis and Toxicity - Stern, Martin (Verlag Wissenschaftliche Scripten, 2003)
A collection of papers presented at a congress that focused on food analysis and toxicity testing regarding the presence of prolamin. Intended for professional public.
Keywords: environmentální vědy; zemědělství a potravinářství; Food Analysis; prolaminy; Toxicity Tests; Food Safety; analýza potravin; bezpečnost potravin; testy toxicity; Prolamins